Fractional ablative carbon dioxide laser treatment of facial scars: improvement of patients' quality of life, scar quality, and cosmesis - Meynköhn, Anna Lucca; Fischer, Sebastian; Neuss, Clara; Willkomm, Lina-Marie; Kneser, Ulrich; Kotsougiani-Fischer, Dimitra (Journal of cosmetic dermatology, 2021)
Background Disfiguring facial scars can be a massive burden on patients' psychosocial health and severely impact patients' self-esteem. Aims The aim of this study was to analyze whether ablative fractional carbon dioxide laser (CO2-AFL) treatment can positively influence facial scarring and quality of life (QoL) while improving the aesthetic appearance. Patientes/Methods Patients with facial scars who had received CO2-AFL treatment between May 2019 and May 2020 were included in a retrospective study. The post-interventional course and patient and/or observer reported outcomes were inquired before and three months after treatment. Primary outcomes were changes in the Patient and Observer Scar Scale (POSAS) and QoL (Short Form (SF) 36). In addition, two independent examiners evaluated the aesthetic outcome by comparing initial scarring with the post-intervention results using photographs. Results A total of 16 patients with facial scars were included. Most of the scars were caused by burns (43.8%) or trauma (31.3%). The post-interventional course was uneventful. Overall POSAS scores improved decisively for both observers (n=2) and patients (n=16) (p<0.001 and p<0.001). Also, there was an improvement in QoL with an increase in emotional well-being (p=0.043) and social functioning (p=0.01). Furthermore, the aesthetic outcome was significantly enhanced (p=0.001) after treatment. Conclusion The CO2-AFL offers a safe and effective treatment for disfiguring facial scars. We have shown that improvement of scar appearance and scar quality was meaningful to the patient, with a significant impact on a patient’s life quality. Based on these findings we suggest including the CO2-AFL in the facial scar treatment concept.
First published: 18 November 2020
Gesehen am 17.08.2021